Beginning Xcode - Bucanek, James, 1965- (Wrox beginning guides., 2006)
Xcode is a powerful suite of free development tools from Apple Computer that will allow you to create Macintosh applications, plug-ins, web components, applets, and more using languages such as C, C++, Objective-C, Java, and AppleScript. What you will learn from this book:Control window layout to match your development style.